Cooperative goals in the Chinese work environment: a Hong Kong case study - Ng, Peter; Nowak, Margaret; Whiteley, Alma (Routledge, 2008)
This research seeks to develop an understanding of how cooperative teamwork among Chinese employees impacts upon the customer perception of service in the Hong Kong ship-repair industry. The research model was based on the 'Theory of Cooperation and Competition', a western-conformity. The results suggested the need to explore alternative processes that Chinese people may engage in in managing their conflict. We question whether the 'goals' or 'ends' based approach to the operation of teams inherent in the Theory of Cooperation and Competition, is valid in the Chinese context where 'process' and 'relationship' are pivotal.